Функціональне діагностування енергетичної ефективності асинхронного електропривода промислових установок і механізмів протягом життєвого циклу - Праховник, Артур Веніамінович; Закладний, Олександр Миколайович; Закладний, Олег Олександрович (НТУ "ХПІ", 2010)
The report considered energy efficiency and protection of asynchronous electric life cycle by controlling the parameters of its current mode and real-time diagnosis and evaluation of energy and technical conditions to make informed decisions on further exploitation by identifying inefficient and emergency operating modes, predicting their development and determination of residual life.
Functional diagnostics asynchronous electric drives energy efficiency of industrial plants and mechanisms during life cycle
Keywords: електрообладнання; навантаження електромеханічне; модель математична; температура; показники якості електроенергії